Community ecology of the metazoan parasites of snoek Thyrsites atun (Euphrasen, 1791) (Perciformes: Gempylidae) off South Africa. Issue 3 (23rd September 2016) - Nunkoo, MAI; Reed, CC; Kerwath, SE
Abstract : The parasite assemblage of snoek Thyrsites atun, a commercially important fish in the Benguela system, was examined over a one-year period. In all, 16 parasite taxa including eight new host records ( Bolbosoma vasculosum, Caligus coryphaenae, Caligus dakari, Corynosoma australe, Hatschekia conifera, Nothobomolochus fradei, Rhadinorhynchus cadenati, Tentacularia coryphaenae ) and four new locality records ( B. vasculosum, C. dakari, Molicola uncinatus, Pseudoterranova sp.) were recovered from 210 specimens. The dominance of larval helminths in the component community suggests that T. atun occupies an intermediate position in the food web. The 'nestedness metric based on overlap and decreasing fill' (NODF) indicated that the parasite assemblage exhibited no nestedness (NODF = 73.3, p = 0.103). Generalised additive mixed modelling results indicated that host length is the main determinant of parasite species richness in T. atun . PERMANOVA and ANOSIM suggested that infracommunity structure varied little with respect to the sex, length, seasonality and capture region of the host. The stability and randomness in parasite acquisition, as indicated by the lack of nestedness of the parasite assemblage, can be ascribed to the opportunistic feeding behaviour and nomadic movement of T. atun in the southern Benguela. The homogeneity of the community structure of long-lived endoparasites suggests that a single T. atun stock occurs off South Africa.